Аналіз ефективності застосування способів запобігання надзвичайних ситуацій на полігонах депонування відходів - Рашкевич, Ніна Владиславівна (НТУ "ХПІ", 2017)
У роботі проведений аналіз ефективність застосування способів раннього виявлення мікро джерел надзвичайних ситуацій (пожеж) на полігонах депанування відходів. Обґрунтована доцільність використання дистанційних методів контролю ступеня забруднення атмосферного повітря, визначення первинних ознак пожежі (підвищенні температури, наявністю токсичних речовин). Встановлені потреби підвищення достовірності результатів досліджень шляхом врахування значного числа змінних факторів при математичному моделюванні фізико-хімічних процесів на території полігонів. Результати досліджень представляють практичний інтерес при забезпеченні техногенно-екологічній безпеці у сфері поводження з відходами.

In the work the analysis of scientific studies that are associated with using contact, remote and biological methods for pollution control and early detection of micro fire sources in the body of the landfill with waste. Found that control air quality primarily is based on laboratory chemical sampling and analysis of samples to obtain statistical information without identifying the specific contribution of contaminants from disposal sites. Remote monitoring tools (GIS-technology, laser system) are an effective way of detecting contamination, as well as the origin of the primary signs of fire. Indicators of the initial stage of the emergency there may be toxic substances or the increase in air temperature above the surface of the landfill. Need of increase of reliability of research results by taking into account the significant number of variables in the mathematical modeling of physicochemical processes on the territory of polygons. The research results are of practical interest in ensuring technogenic-ecological safety in the sphere of waste management.
Analysis of the effectiveness of methods of prevent emergencies at the landfill depositing waste
Keywords: безпека; засоби контролю; моніторинг; ГІС-технології; лазерний комплекс; НС; тверді побутові відходи; геоінформаційні системи; safety; emergency situations; means of control